Aktivitas Antiinflamasi Ekstrak Daun Tembelekan (Lantana camara Linn) pada Tikus Putih (Rattus norvegicus) - Aji Yudha Wijaya; Muhammad Amir Masruhim; Hadi Kuncoro (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2016)
A study of anti-inflammatory activity of tembelekan leaf extract (Lantana Camara Linn) in white rat (Rattus norvegicus) has done. This study aimed to determine the effective doses of Tembelekan leaf extract which giving an anti-inflammatory effect artificial edema in the feet of the rat. The method was artificial edema formatting and measuring the volume of white rat feet an o regular basis by a plethysmometer. The used doses were 750mg/kgBB, 1000mg/kgBB, 1250mg/kgBB dan 1500mg/kgBB. The data were further processed by using analysis of variance (Anova) two away, advance testing HSD test (Honestly Significance Difference Duncan). The result of this research is the effective dose of tembelekan leaf extract is 1500mg/kgBB wich as an anti-inflammatory effect better than 750mg/kgBB, 1000mg/kgBB, 1250mg/kgBB